Challenges facing international social workers: English managers' perceptions. (November 2016) - Hanna, Sue; Lyons, Karen
International labour mobility is occurring in social work and isolated studies are beginning to research this topic. This article reports on one aspect of research into the experiences of 'international social workers' (ISWs) in London (UK), namely, the perceptions of the managers who supervise them, with regards to their preparedness, induction and support needs.